FEATURES OF THE IMPLEMENTATION OF VIRUS ATTACKS IN AUTOMATED SPECIAL PURPOSE SYSTEMS (Academia Science Repository, 2023)
Automated special-purpose systems have grown in significance in contemporary society as a result of its various advantages, including improved productivity, precision, and speed of operation. The potential of cyberattacks, which can jeopardize the security, integrity, and accessibility of the data stored and processed by these systems, is present as a result of the growing usage of these systems. Traffic analyzers, keyloggers, software that implements the effects of "denial of service" (DoS, DDoS), "man in the middle" (MITM), and software that provides "session interception" (HTTP) are currently the most prevalent software products developed on the basis of virus technologies, which are actively used in the implementation of virus attacks in the class of systems similar to the ASSN ATS. Virus assaults, in particular, may seriously harm automated special-purpose systems since they are intended to proliferate quickly and infect several computers or other devices connected to a network.